The immediate influence of implicit motor learning strategies on spatiotemporal gait parameters in stroke patients: a randomized within-subjects design. (April 2019) - Kleynen, Melanie; Jie, Li-Juan; Theunissen, Kyra; Rasquin, Sascha MC; Masters, Rich SW; Meijer, Kenneth; Beurskens, Anna J; Braun, Susy M
Objectives: To investigate immediate changes in walking performance associated with three implicit motor learning strategies and to explore patient experiences of each strategy. Design: Participants were randomly allocated to one of three implicit motor learning strategies. Within-group comparisons of spatiotemporal parameters at baseline and post strategy were performed. Setting: Laboratory setting. Subjects: A total of 56 community-dwelling post-stroke individuals. Interventions: Implicit learning strategies were analogy instructions, environmental constraints and action observation. Different analogy instructions and environmental constraints were used to facilitate specific gait parameters. Within action observation, only videotaped gait was shown. Main measures: Spatiotemporal measures (speed, step length, step width, step height) were recorded using Vicon 3D motion analysis. Patient experiences were assessed by questionnaire. Results: At a group level, three of the four analogy instructions ( n  = 19) led to small but significant changes in speed ( d  = 0.088 m/s), step height (affected side d  = 0.006 m) and step width ( d  = –0.019 m), and one environmental constraint ( n  = 17) led to significant changes in step width ( d  = –0.040 m). At an individual level, results showed wide variation in the magnitude of changes. Within action observation ( n  = 20), no significant changes were found. Overall, participants found it easy to use the different strategies and experienced some changes in their walking performance. Conclusion: Analogy instructions and environmental constraints can lead to specific, immediate changes in the walking performance and were in general experienced as feasible by the participants. However, the response of an individual patient may vary quite considerably.